Magical Feminism: The Female Voices of Magic Realism in Isabel Allende’s The House of the Spirits and Laura Esquivel’s Like Water for Chocolate - Selvarani, R. Ranjini; Hussain, Dr. M. S. Zakir (International Journal of English Literature and Social Sciences (IJELS), 2019)
Magic realism is a distinct subgenre of writing that works on the mechanism of paradoxes of placing two opposites together to make a rich and complex meaning – the fusion of real and fantastic as Angel Flores calls it ‘amalgamation of realism and fantasy’. Magic Realism can also be read as a Postcolonial weapon as it fight backs the traditional tendencies and the staunch realism of western literature. Female voices have also employed magic realism to say aloud the problems of women across the globe. Magic Realism has thrived well in the hands of women writers across cultures and continents. Toni Morrison, Isabel Allende, Laura Esquivel, Chitra Divakaruni Banerjee, Arundhathi Roy, Sarah Addison Allen, Yaa Gyasi, Raja Alem etc. This paper proposes to bring into limelight the Latin American Women Writers who are often left out to be mentioned along the list of men Latin American writers.